BACK TO THE PREHISTORY OF ON-SCREEN COMPUTER MISE-EN-SCENE / К ПРЕДЫСТОРИИ ВНУТРИЭКРАННОЙ МИЗАНСЦЕНЫ КОМПЬЮТЕРА НА «РАБОЧЕМ СТОЛЕ» И ЗА ЕГО ПРЕДЕЛАМИ - SALNIKOVA E.V. / САЛЬНИКОВА Е.В. (Наука телевидения, 2016)
The article discusses the on-screen reality of the computer, where the visual arrangement of signs on the screen folds into inner computer mise-en-scene. The right to rule in the relations with the computer smooths and compensates for man-Hector the state of social powerlessness, economic pressure and emotional loneliness. Lost magical universe returns to the man of our age in the form of virtual space transition on the «desktop» and on the other side of the «desktop».